PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA PADA MATERI PENCEMARAN LINGKUNGAN KELAS VII SMP NEGERI 2 DOLOK PANRIBUAN TAHUN PELAJARAN 2019/2020 - Lestari Sinaga, Ayu; Lihardo Hulu, Irwan (Jurnal Metabio, 2021)
This study aimed to determine the effect of the problem-based learning (PBL) model on students' science learning outcomes on environmental pollution in grade VII of SMP Negeri 2 Dolok Panribuan in the even semester of the 2019/2020 academic year. The study used a quasiexperimental method with a posttest-only control design. The sample of this study was 66 grade VII students of SMP Negeri 2 Dolok Panribuan. The research instrument was a test divided into a pre-test (given before learning) and a post-test (given after learning with different treatments). The pre-test and post-test were conducted in the form of 20 multiple-choice questions. Each correct answer was given a score of 5 and an incorrect answer was given a score of 0. Thus, the score range was 0-100. The prerequisite techniques for data analysis were normality and homogeneity tests. Furthermore, the data were analyzed by calculating the average score (mean) and the magnitude of the standard deviation (S). Based on the research results, the total post-test score of the experimental class was 3155 with an average score of 95.60, and the total post-test score of the control class was 3050 with an average learning outcome score of 92.61 with a difference of 3.19. Based on the results of the hypothesis testing, in the t-test, the calculated t = 2.13 was obtained and at the significance level of ɑ = 0.05 and df = 32, the obtained t table = 2.03. So, t count > t table, then H0 is rejected and Ha is accepted, meaning there is an effect of the use of problem-based learning models on students' science learning outcomes on environmental pollution material for class VII of SMP Negeri 2 Dolok Panribuan in the 2019/2020 academic year. Based on the results of the correlation test, the problem-based learning model has an effect on students' science learning outcomes on environmental pollution material for class VII of SMP Negeri 2 Dolok Panribuan in the 2019/2020 academic year.